Current clinical practices in pediatric audiology among audiologists in India - Twinkle Lijo Kirianthan; Dhanshree R. Gunjawate; Rohit Ravi (PLoS ONE, 2026)
Objective Evidence-based practice is central to audiology; however, adherence to best-practice guidelines varies, particularly in pediatric settings. This study explored current pediatric audiology practices among audiologists in India. Methods A cross-sectional survey was conducted using an adapted version of the American Board of Audiology’s Pediatric Audiology Clinical Practice Analysis Survey modified for the Indian context. The survey was distributed electronically via email using contact information available with Rehabilitation Council of India (RCI). Eligible participants held at least a bachelor’s degree in Audiology and Speech-Language Pathology and had a minimum of one year of clinical experience. Participation was voluntary, informed consent was obtained, and confidentiality of responses was ensured. Descriptive statistical analyses were performed. Scale content validity index was calculated to assess content validity of the questionnaire. Results A total of 130 audiologists participated, representing a predominantly early-career workforce (mean experience = 4.92 ± 5.41 years). Core pediatric audiology procedures were widely practiced. Newborn hearing screening was considered very important by 66.2% of participants, while 35.4% performed it several times daily. Tympanometry was rated very important by 61.5%, with 40% performing it several times daily. Counselling-related practices were strongly emphasized, with 68.5% rating explanation of test results as very important and 48.5% performing it several times daily. In contrast, advanced procedures demonstrated lower utilization. Cortical evoked potentials were not performed by 35.4% of participants, vestibular assessments by 43.1%, cochlear implant programming by 45.4%, and bone conduction device management by 57.7%. Conclusions Indian audiologists consistently provide essential pediatric audiology services; however, gaps persist in specialized diagnostics and rehabilitation. Enhancing infrastructure, professional training, and adherence to evidence-based guidelines is necessary to strengthen pediatric audiological care in India.